Development of Learning Media Assisted by iSpring Suite with Discovery Learning Model to Facilitate Mathematical Understanding Ability - Ningrum, Rosilawati Kusuma; Suanto, Elfis; Hutapea, Nahor Murani (Universitas Riau, 2024)
The purpose of this research is to produce learning media that can facilitate students' mathematical understanding abilities on circle material assisted by iSpring Suite 10 software with a Discovery Learning model that can be accessed on Android smartphones and laptops and has met the valid and practical requirements. The development model used is the 4D model, with the stages of define, design, develop, and disseminate. The learning media was validated by three media experts, and the research subjects involved three students in one-on-one activities, six students in small group trials, and 30 students in large group trials. The research instruments included validation sheets and student response questionnaires. The results of validation by experts obtained an average of 90.6% with very valid criteria. Feedback and suggestions obtained from validation and one-to-one were used as improvement materials. Furthermore, small group and large group trials were carried out, each of which obtained an average of 91.87% and 91.58% with very practical criteria. This iSpring Suite 10 assisted learning medium with the Discovery Learning model on circle material to facilitate the mathematical understanding ability of junior high school students has met the valid and practical criteria.